Empirical Study of Humor Support in Social Human-Robot Interaction - Bechade, Lucile; Duplessis, Guillaume Dubuisson; Devillers, Laurence (Distributed, Ambient and Pervasive Interactions, 2016)
As part of the Joker project which provides a multimodal dialog system with social skills including humor and empathy, this paper explores idea concerning the human verbal responses to a joking robot. Humor support is defined as the conversational strategies used in reaction to humor utterances. This paper aims at exploring the phenomenon of responses to humor interventions from the robot through the examination of a corpus. We assume that using humor in human-robot interaction sets up a positive atmosphere in which participants are willing to contribute. This study relies on 49 human-robot interaction dialogues and 381 adjacency pairs of humorous acts made by the robot and the following human responses. The human humor responses, elicited through canned jokes and conversational humor, were annotated. Three main categories of human responses were found (1) providing no support, (2) recognizing the attempt of humor and (3) contributing with more humor. The findings indicate that, as in human-human interaction, strategies of humor support are strongly dependent of the humorous event’s context.